2019
DOI: 10.2147/cia.s189417
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optical coherence tomography angiography features in patients with idiopathic full-thickness macular hole, before and after surgical treatment</p>

Abstract: PurposeTo present optical coherence tomography (OCT) angiography features in patients with idiopathic full-thickness macular hole before and after vitrectomy.Study designProspective case series study.Materials and methodsPatients presenting with an idiopathic full-thickness macular hole (IMH) who underwent posterior vitrectomy with internal limiting membrane peeling and gas tamponade were included in the study. En face OCT and OCT angiography (OCTA) was performed pre- and postoperatively using 3×3 mm scans (Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
2
31
0
4
Order By: Relevance
“…Mean FVDS in SCP was 29.84% ± 4.17% preoperatively and increased to 35.02% ± 3.47% postoperatively. They found a relatively strong correlation between preoperative FAZ and postoperative BCVA [ 24 ]. In our patients, the best results in OCTA images presented Case 2 with the lowest FAZ and the highest FVDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean FVDS in SCP was 29.84% ± 4.17% preoperatively and increased to 35.02% ± 3.47% postoperatively. They found a relatively strong correlation between preoperative FAZ and postoperative BCVA [ 24 ]. In our patients, the best results in OCTA images presented Case 2 with the lowest FAZ and the highest FVDS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported characteristics of OCTA images in eyes with FTMH or comparison of OCTA images before and after surgery [ 22 24 ]. Analysis of OCTA images in eyes after secondary vitrectomy due to FTMH should be performed in a bigger sample of patients and compared with the group of patients with successful first surgery.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA is a novel imaging technique that utilizes motion contrast to visualize retinal microvasculature in a rapid, noninvasive way. To date, several studies have reported vascular changes and quantitative characteristics of OCTA images in eyes with MH, considering this new technique to be a useful tool for the assessment of MHs before and after surgical treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative findings were increased foveal vascular density in the superficial plexus, increased flow area in the choriocapillaris, and a reduced foveal avascular zone. These anatomic and hemodynamic changes implied that the recovery process of the inner retina has neuronal and vascular plasticity [20].…”
Section: Discussionmentioning
confidence: 99%